2013
DOI: 10.2174/1570159x11311050003
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Treatments for Cocaine Dependence in Schizophrenic Patients: A Systematic Review

Abstract: Objectives:To evaluate and compare the effectiveness of available treatments for cocaine dependence in schizophrenic patients. Method: We searched articles published between May 2002 and June 2012 in the following databases: Scopus, Pubmed and Web of Knowledge. The key words utilised were “schizophrenia”, "dementia praecox", "schizophrenic disorder", "cocaine related disorder", "cocaine abuse", "cocaine addiction", "cocaine dependence", “treatment”, “therapeutic”, and "drug therapy”. Selection of studies and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…Other atypical antipsychotics, like risperidone, olanzapine, or reserpine, were no more effective in reducing psychostimulant consumption than placebo when considered in a meta-analysis Kishi, Matsuda, Iwata, & Correll, 2013). Similar conclusions were reached when antipsychotics were considered as a treatment of cocaine addiction in schizophrenic patients (Sabioni, Ramos, & Galduroz, 2013).…”
Section: Antipsychoticssupporting
confidence: 69%
“…Other atypical antipsychotics, like risperidone, olanzapine, or reserpine, were no more effective in reducing psychostimulant consumption than placebo when considered in a meta-analysis Kishi, Matsuda, Iwata, & Correll, 2013). Similar conclusions were reached when antipsychotics were considered as a treatment of cocaine addiction in schizophrenic patients (Sabioni, Ramos, & Galduroz, 2013).…”
Section: Antipsychoticssupporting
confidence: 69%
“…In addition, a systematic review of 14 placebo-controlled studies investigating the use of antipsychotics for cocaine dependence from the Cochrane Collaboration did not find significant differences in any of the outcome variables analyzed, including the number of patients using cocaine during treatment, continuous abstinence and craving [41], supporting the results of a previous meta-analysis on the use of antipsychotics for cocaine or psychostimulant use disorder [42]. Focusing on patients with a dual disorder diagnosis, another systematic review concluded that the efficacy of antipsychotics for cocaine dependence in patients with schizophrenia has not been robustly demonstrated [43]. Although the sample size precludes any conclusion, it is worthy to mention that the three patients with heroin use disorder at baseline achieved abstinence at the end of the follow-up.…”
Section: Discussionsupporting
confidence: 65%
“…Aripiprazole, a second-generation antipsychotic drug also used in the treatment of depression, has shown no efficacy in clinical trials of cocaine-use disorder (Sabioni, Ramos, & Galduroz, 2013) or methamphetamine-use disorder (Coffin et al, 2013; Sulaiman et al, 2013). …”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“… The following reviews were included in the manuscript but not in this table: Garbutt, 2010; Herin et al, 2010; Mereu et al, 2013; Sofuoglu et al, 2013; Soares et al, 2003; Lima et al, 2003; Pani et al, 2011; Sabioni et al, 2013; Minozzi et al, 2008; Lima et al, 2002; Gardner & Kosten, 2007; Kosten & Domingo, 2013; Ishizaka & Hawkins, 2007. CBT – Cognitive Behavioral Therapy; BE – benzoylecgonine; SR – sustained release; IR – immediate release; IV – intravenous; …”
Section: Tablementioning
confidence: 99%